Bankziska as Lazismu Innovation and BMT Hasanah in Economic Empowerment in Ponorogo - Faizin, Moh Faizin; Futaqi, Faruq Futaqi; Nurhidayati, Maulida (LAA MAISYIR : Jurnal Ekonomi Islam, 2021)
The purpose of this study is to analyze the innovations made by Lazismu East Java with BMT Hasanah Ponorogo named BankZiska. The analysis method used in this study is descriptive-qualitative and interpretive techniques. The findings of this study are Bankziska stands for Zakat-based Financial Assistance Infak Shodaqoh and Other Religious Social Funds. Bankziska’s capital source is obtained from Lazismu and BMT Hasanah where bankziska management is implemented by BMT Hasanah. BankZiska provides interest-free, unsecured, no-fines, no-fee, and no-f confiscated loans to micro, micro and small super-entrepreneurs affected by loan sharks (interest). Another benefit of BankZiska is the existence of religious assistance for entrepreneurs who make loans.